Emergency Remote Teaching and Nursing Education during the COVID-19 pandemic: A narrative review (Research, Society and Development, 2023)
Given the challenges posed by the COVID-19 pandemic, teaching practices, especially in nursing, underwent significant transformations. In response to this global public health crisis, it became imperative to reassess academic education, its impact, and the necessary adaptations. This review aims to explore and analyze key scientific productions related to Emergency Remote Teaching and nursing education during the COVID-19 pandemic. It is a narrative review conducted on the Lilacs, Medline, and BDENF databases between the years 2020 and 2023, using health descriptors such as pandemic, teaching, nursing, and COVID-19. The results and discussions from the analysis of the 24 selected articles showed that Emergency Remote Teaching in nursing education was essential for maintaining the training process for nurses in Brazil. Numerous challenges were encountered, such as the rapid implementation of the teaching model and its various pedagogical approaches. However, many articles express a positive view of the use of Emergency Remote Teaching, as perceived by educators and students involved in the nursing teaching and learning process. It is concluded that the use of Emergency Remote Teaching in nursing during the pandemic was crucial for maintaining the training of nursing professionals in a critical period of health crisis. It is essential to emphasize that assessment and adaptation measures are necessary to enhance the teaching process through this model and ensure quality nursing education.